Islam in West Africa: Religion, Society and Politics to 1800 by Nehemia Levtzion. Aldershot, Brookfield: Ashgate Publishing Limited. 1994. (American Journal of Islam and Society, 1997)
Islam in West Africa is a collection of nineteen essays written by NehemiaLevtzion between 1963 and 1993. The book is divided into five sections. dealingwith different facets of the history and sociology of Islam in West Africa.The first section focuses on the patterns, characteristics, and agents of thespread of Islam. The author offers an approach to the study of the process of thatIslamization in West Africa that compares pattems of Islamizacion in medievalMali and Songhay to patterns in the Volta basin from the seventeenth to thenineteenth centuries. He also assesses the complex roles played by Africanchiefs and kings and slavery in the spread of Islam.Section two focuses on the subject of lslam and West African politics fromthe medieval period to the early nineteenth century. Levtzion identifies twotrend in African Islam: accommodation and militancy. Islam's early acceptancein West African societies was aided by the fact that Islam was initially seen asa supplement, and not as a substitute, to existing religious systems. Levtzionanalyzes the dynamics of Islam in African states as accommodation gave wayin time to tensions between the ruling authorities and Islamic scholars, callingfor a radical restructuring of the stare according to Islamic ideals. The tensionsbetween the Muslim clerics of Timbuktu and the medieval Songhay rulers. andthe ultimately adversarial relationship between Uthman dan Fodio and the Gobirleadership in eighteenth-century Hausaland, are singled out for sustained analysis ...